AN ERROR ANALYSIS OF THE STUDENT’S WRITING IN PASSIVE VOICE AT SMK PASUNDAN 1KOTA SERANG - Irma Handayani; Sisca Wulansari Saputri; Aa Qonaatun (FKIP, Universitas Banten Jaya, 2018)
In constructing correct passive voice, students need to master grammar. In this case, learning passive voice always creates errors. The objectives of this research were to know the types of Passive Voice that taught in SMK Pasundan 1 kotaSerang ateleventhgrade and to find out the causes of errors made by the student’s Writing Passive Voice especially Simple Past Tense. The subjects of this research consisted of 15 students at eleventh grades of SMK Pasundan 1 Kota Serang. The method of this research was Qualitative by using Case Study Method. To collect the data the writer used test as an instrument, while the writer was analyzed errors of the students it is based on the Surface Strategy Taxonomy. The results of this research are Misformation errors consisted 41 errors or 58,57 %, followed by Omission errors consisted 23 errors or 32,58 %, Misordering error consisted 5 errors or 7,14 % and Addition error consisted 1 errors or 1,43 %. Based on the result of the research the dominant errors was Misformation consisted 58,57%. The conclusion of this research was this research related to a cause error made by the students and one of the cause was less understanding about grammar especially Simple Past Tense.